The constitutional principle of advertising and the Eletronic Judicial Process (PJe): challenges for guaranteeing the fundamental right of access to information (Research, Society and Development, 2021)
The implementation of the “PJe” from Resolution 185 of the National Council of Justice brought a series of changes related to access to procedural information, reaching everyone, including the parts. The Constitution of the Republic brings in its text the fundamental right of access to justice. It also foresees the Publicity of the acts of the Public Administration. We sought to problematize the “PJe” against the constitutional commandments, in order to contribute to the doctrinal debate on access to information within the Judiciary. For this, the legal-theoretical method and deductive reasoning were used, with bibliographic research technique. It was found that the administration of the Judiciary must be based on the principle of sustainable development in order for access to justice to occur fully.